1994
DOI: 10.1007/bf02815362
|View full text |Cite
|
Sign up to set email alerts
|

Preferential binding of the epidermal growth factor receptor to ganglioside GM3 coated plates

Abstract: Ganglioside GM3 has been shown to modulate epidermal growth factor receptor function. These observations have lead to the hypothesis that GM3 may bind to the epidermal growth factor receptor. An enzyme-linked immunosorbant assay was designed to test this hypothesis. In these experiments, receptor-rich vesicle preparations were incubated with ganglioside GM1 or GM3 coated 96-well microtiter plates and the amount of bound receptor was compared. Plates coated with GM3 consistently bound more epidermal growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…For example, GD3 and GD2 coimmunoprecipitate with ␣ v ␤ 3 (40); given the structural similarities between the ␣ 5 ␤ 1 and ␣ v ␤ 3 integrins, it is likely that the ganglioside-␣ v ␤ 3 interaction similarly involves carbohydratecarbohydrate recognition of the extracellular N-terminal region of ␣ v . Studies in 1988 first demonstrated that ganglioside GM3 co-immunoprecipitates with the epidermal growth factor receptor (EGFR) (41), and this ability to complex was further suggested by ELISAs (42). In fact, we have recently provided evidence that the relationship between GM3 and the EGFR that is required for inhibition of EGFR activation involves carbohydrate-carbohydrate interaction.…”
Section: Discussionmentioning
confidence: 98%
“…For example, GD3 and GD2 coimmunoprecipitate with ␣ v ␤ 3 (40); given the structural similarities between the ␣ 5 ␤ 1 and ␣ v ␤ 3 integrins, it is likely that the ganglioside-␣ v ␤ 3 interaction similarly involves carbohydratecarbohydrate recognition of the extracellular N-terminal region of ␣ v . Studies in 1988 first demonstrated that ganglioside GM3 co-immunoprecipitates with the epidermal growth factor receptor (EGFR) (41), and this ability to complex was further suggested by ELISAs (42). In fact, we have recently provided evidence that the relationship between GM3 and the EGFR that is required for inhibition of EGFR activation involves carbohydrate-carbohydrate interaction.…”
Section: Discussionmentioning
confidence: 98%
“…To confirm that gangliosides remained coated on the plates during the assay, anti-ganglioside antibodies directed against GM1 and GM3 were used in place of the LA22 antibody. Equivalent binding of both anti-GM3 and anti-GM1 antibodies was observed, indicating that there was no preferential loss of gangliosides (18).…”
Section: Expression and Purification Of The Recombinant Ecd-inmentioning
confidence: 94%
“…The ganglioside interaction assay was carried out using an assay similar to that described for the full-length EGFR (18). The amounts of gangliosides used for coating the plates varied from 10 to 5000 pmol (Fig.…”
Section: Expression and Purification Of The Recombinant Ecd-inmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique transition state III is supported by ligand-binding experiments. GM3 did not affect ligand binding to the full-length EGFR (16,36) and in binding assays with recombinant EGFR the GM3 binding site was separate from the EGF binding site (30). However, in keratinocyte-derived SCC12 cells, EGF binding to the EGFR is inhibited by GM3 (37).…”
Section: Mechanisms Of Growth Factor Receptor Modulation By Gangliosidesmentioning
confidence: 97%